2019
DOI: 10.1126/sciadv.aax0801
|View full text |Cite
|
Sign up to set email alerts
|

Covalently tethering siRNA to hydrogels for localized, controlled release and gene silencing

Abstract: Small interfering RNA (siRNA) has found many applications in tissue regeneration and disease therapeutics. Effective and localized siRNA delivery remains challenging, reducing its therapeutic potential. Here, we report a strategy to control and prolong siRNA release by directly tethering transfection-capable siRNA to photocrosslinked dextran hydrogels. siRNA release is governed via the hydrolytic degradation of ester and/or disulfide linkages between the siRNA and hydrogels, which is independent of hydrogel de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Importantly, chemical modification of RNA for covalent bonding may impede cell internalization as observed by Nguyen et al. [ 116 ] (see Section 4.3 ). Therefore, cleavage of covalently linked RNA should ideally release the RNA in unmodified form.…”
Section: Modulating Rna Delivery From Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, chemical modification of RNA for covalent bonding may impede cell internalization as observed by Nguyen et al. [ 116 ] (see Section 4.3 ). Therefore, cleavage of covalently linked RNA should ideally release the RNA in unmodified form.…”
Section: Modulating Rna Delivery From Biomaterialsmentioning
confidence: 99%
“…However, chemical modification of RNA may impede its cellular internalization, as illustrated by Nguyen et al. [ 116 ], who covalently bound thiol end-modified siRNA to a hydrogel of mono (2-acryloyloxyethyl) succinate–modified dextran using hydrolytically cleavable β-thioether ester linkages. They demonstrated that the delivery of covalently bound siRNA was significantly slower compared to unbound siRNA lacking this thiol modification (30% vs 68% release after 24 ​h for bound and unbound siRNA, respectively).…”
Section: Modulating Rna Delivery From Biomaterialsmentioning
confidence: 99%
“…Likewise, in an effort to control the release kinetics and preserve the activity of therapeutic biomolecules, hydrogels have been widely investigated as gene delivery systems [ 15 ]. Various hydrogels systems based on natural polymers such as alginate [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]; cellulose [ 40 ]; chitosan [ 41 , 42 , 43 , 44 ] ( Table 1 ); collagen [ 45 , 46 , 47 ]; dextran [ 48 ]; fibrin [ 17 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]; pullulan [ 56 ] ( Table 1 ); gelatin [ 57 , 58 , 59 , 60 ]; hyaluronic acid (HA) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] ( Table 1 ); or synthetic ones as polyethylene-glycol (PEG) [ 70 , 71 , 72 , 73 ,…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, controlled delivery of RNA molecules from hydrogels networks may enhance local and sustained siRNA [ 43 , 44 , 48 , 49 , 56 , 59 , 71 , 75 , 76 , 78 , 79 , 85 , 86 ] and miRNA [ 46 , 47 , 60 , 62 , 63 , 80 , 81 , 82 , 84 , 92 ] delivery limiting undesired targets [ 14 ], and protect mRNA nanoparticles from the biological environment improving their cellular access [ 17 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Given the challenges that RNAi-based drugs would encounter, using nanoparticles as vectors is likely to reduce these obstacles, followed by enhancing cellular uptake of siRNAs and optimizing silence efficacy. 9 Therefore, this mini-review aims to briefly describe the fundamental mechanisms of RNAi machinery and provide insights on the current status on the use of nanoparticles for siRNA delivery, as well as to discuss the applications of siRNA in cancer research and clinical therapy.…”
mentioning
confidence: 99%